A retrospective analysis of the diagnostic utility of endobronchial ultrasound guided–intranodal forceps biopsy (EBUS-IFB) in the evaluation of mediastinal adenopathy - Richu Bob Kurien; Priya Nadesan; Balamugesh Thangakunam; Barney Isaac; Thomas Alex Kodiatte; Reka Karuppusami (The Egyptian Journal of Bronchology)
Abstract Background Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is the preferred diagnostic modality for evaluating mediastinal lymphadenopathy. However, its diagnostic yield is significantly reduced in conditions such as sarcoidosis, tuberculosis, and lymphoma. To address this limitation, EBUS-guided intranodal forceps biopsy (EBUS-IFB) has been proposed as an adjunct technique to enhance diagnostic accuracy in these challenging cases. This study aimed to evaluate the diagnostic yield of EBUS-IFB in the assessment of mediastinal lymphadenopathy. Methods We retrospectively reviewed patients with mediastinal lymphadenopathy who underwent EBUS-guided intranodal forceps biopsy (EBUS-IFB). Diagnostic yield was determined using a composite reference standard (CRS), which was considered positive if a definitive diagnosis was established by any of the following: rapid on-site evaluation (ROSE), EBUS-TBNA, EBUS-IFB, bronchial biopsy, or transbronchial lung biopsy. To specifically evaluate the incremental diagnostic yield of EBUS-IFB, cases with non-diagnostic ROSE results were analysed separately. Results Of the 40 cases with undiagnosed mediastinal lymphadenopathy, CRS was obtained in 31 cases (77.5%), while the remainder were diagnosed as reactive lymphadenopathy. Sampling adequacy was achieved in 39 out of 40 cases (97.5%). The overall diagnostic yield for EBUS-TBNA, EBUS-IFB, and combined EBUS-TBNA along with IFB (combined approach) were 54.8%, 83.9% (p value:0.03), and 90.3% (p value: 0.004) respectively. The additional diagnostic yield for EBUS-IFB and the combined approach (EBUS-TBNA + IFB) were 29.0% and 35.5% respectively, as compared to EBUS-TBNA alone. The sensitivity and specificity EBUS-IFB were 84% and 100% respectively. In subgroup analysis for cases with non-diagnostic ROSE, the diagnostic yield for EBUS-TBNA, EBUS-IFB, and the combined approach (EBUS-TBNA + IFB) were 48.2%, 85.2% (p value: 0.009) and 88.9% (p value: 0.003) respectively. The additional diagnostic yield for EBUS-IFB and the combined approach (EBUS-TBNA + IFB) were 37.0% and 40.7% respectively, as compared to EBUS-TBNA alone. The sensitivity and specificity of EBUS-IFB when ROSE was non-diagnostic were 85.2% and 100% respectively. No major complications were noted. Conclusion The addition of IFB to routine TBNA significantly improves the diagnostic yield of EBUS, particularly in cases of non-diagnostic ROSE, with no added procedural complications.